The Influence of Environmental Turbulence and Organizational Culture on Financial Performance Through Human Capital Strategies in Educational Technology Start-Ups in Indonesia - Mugi Puspita; Yuniarsih, Tjujtju; Ahman, Eeng; Muhidin, Sambas Ali (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research aims to partially analyze the influence of environmental turbulence and organizational culture on financial performance and examine the role of human capital strategy as a mediating variable on financial performance in education technology start-ups in Indonesia. Descriptive research methods are used to collect data from founders/co-founders of start-ups. up which has been operating for more than five years, with the aim of gaining a deep understanding of the relationships between variables using causality theories existing in the literature. Primary data was collected through a questionnaire with 49 items that explored the variables of environmental turbulence, organizational culture, human capital strategy, and financial performance. Data analysis was carried out using simple linear regression to test the direct relationship between variables, as well as moderation regression analysis to explore the moderating role of human capital strategy in the relationship between independent and dependent variables. Research findings show that environmental turbulence has a negative effect on start-up financial performance, while a strong organizational culture contributes positively to financial performance. Human capital strategy was also found to act as a significant mediator between organizational culture and financial performance. The implications of these findings highlight the importance for start-ups in the educational technology sector to manage the changing environment by developing a strong organizational culture and adaptive human capital strategies. This not only helps improve financial performance, but also strengthens their long-term competitiveness in a competitive market.